2017
DOI: 10.2147/ott.s95322
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of target volumes based on <sup>18</sup>F-FDG PET-CT and ten phases of 4DCT for primary thoracic squamous esophageal cancer

Abstract: PurposeTo investigate the correlations in target volumes based on 18F-FDG PET/CT and four-dimensional CT (4DCT) to detect the feasibility of implementing PET in determining gross target volumes (GTV) for tumor motion for primary thoracic esophageal cancer (EC).MethodsThirty-three patients with EC sequentially underwent contrast-enhanced 3DCT, 4DCT, and 18F-FDG PET-CT thoracic simulation. The internal gross target volume (IGTV)10 was obtained by combining the GTV from ten phases of 4DCT. The GTVs based on PET/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Moreover the median volume variability between the GTV MRI and GTV PET2.5 and between the GTV MRI and GTV CT was statistically significant, while there was no significant difference between GTV PET2.5 and GTV CT , which were accorded with results reported in other literatures 20,21 . Guo et al's analysis 8 demonstrated that GTV PET2.5 resembled better with IGTV 10 , which included GTVs contoured on ten phase of 4DCT. It revealed a trend that 3D PET image included some individualized information derived from respiratory motion.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover the median volume variability between the GTV MRI and GTV PET2.5 and between the GTV MRI and GTV CT was statistically significant, while there was no significant difference between GTV PET2.5 and GTV CT , which were accorded with results reported in other literatures 20,21 . Guo et al's analysis 8 demonstrated that GTV PET2.5 resembled better with IGTV 10 , which included GTVs contoured on ten phase of 4DCT. It revealed a trend that 3D PET image included some individualized information derived from respiratory motion.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the SUV value of PET‐CT selected in delineating GTV may be so low as to including normal periesophageal tissue, which would reduce the accurate in target delineation inevitably. Finally, it should be noted that, the inconsistency of breathing pattern during the acquisition of T 2 W‐MRI and PET‐CT might affect the position and shape of the tumor to some extent 8,12 . As mentioned earlier, the size of GTV derived from MRI was significantly less than that from PET‐CT.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations